Middle Leaders: New essential figures in the management of educational organizations - Olondriz Valverde, Aleix; del Arco Bravo, Isabel (Emerging Trends in Education, 2025)
Educational organizations have constantly evolved throughout history, especially since the late 20th century. The new leadership models, centered on democratization, power distribution, and participation, have led to the creation of new roles for education professionals. Intermediate leadership is a role that many professionals currently develop, establishing a relationship both with senior management and with the rest of the educational community. The objective of this research is to provide an approximation and theoretical analysis of the figure of intermediate leadership. Through the contributions of various studies focused on this leadership model, the new management and leadership distribution needs of educational organizations are related. Subsequently, the three dimensions that shape the leadership profile of intermediate leaders are analyzed: pedagogical, organizational, and relational, as well as the key contribution that this new leadership model can provide to educational management. The results allow for an understanding of the importance of these figures for the positive management of educational organizations, especially in light of the need for senior management to distribute leadership.